Kalendarz Solidarności [kalendarz podziemny] . Solidarity Calendar. Unofficial calendar - NSZZ "Solidarność". (NSZZ "Solidarność", 1984)
Calendar in the form of a booklet (14 pages and a cover), black and red print on white paper. The calendar in a form of a booklet consists of a cover and 14 pages. The front cover carries the title, the back cover carries a graphic image of a group of three workers and a clenched fist. First page contains a quote from Władysław Frasyniuk's appeal to Solidarity supporters issued on 17 December 1981. Last page contains a note field. Each of the remnant 12 pages corresponds to a month and carries graphic image related to the Solidarity movement. Price: 25 zł.